STUDY OF EVOLUTION AND MILESTONES AND PROPERTY MANAGEMENT INCENTIVES IN RUSSIA - S. Sazanova (Вестник университета)
The article deals with the main stages of the evolution of the values of entrepreneurship and business activity, as well as the institutional incentives of management in Russia in XVII - XVIII centuries. The author reveals the factors external and internal environment of the Russian business, influenced the evolution of the economic values; analyzes changes in formal and informal institutions, led to the development of business and entrepreneurial activity in Russia in XVII-XVIII centuries.